Bilateral Multifocal Central Serous-Like Chorioretinopathy due to MEK Inhibition for Metastatic Cutaneous Melanoma. (11th March 2013) - Schoenberger, Scott D.; Kim, Stephen J.
Abstract : Newer chemotherapeutic agents target extracellular signaling, including the mitogen-activated protein kinase kinase (MEK) pathway. We present a case of a 54-year-old female who developed bilateral multifocal central serous-like chorioretinopathy shortly after starting MEK inhibition for metastatic cutaneous melanoma. There was a complete resolution of findings after drug stoppage. After resuming a lower dose of the MEK inhibitor, the findings recurred again but resolved after drug stoppage. Other etiologies were unlikely given the clinical course. The presumed mechanism involves toxicity to the retinal pigment epithelium, with breakdown of the blood-retinal barrier. Recognition of this side effect is important with this new class of chemotherapy.